Bremelanotide for Hypoactive Sexual Desire Disorder: Age and Weight Subgroup Efficacy Analyses [1Q]. (May 2018) - Simon, James A.; Kingsberg, Sheryl A.; Clayton, Anita H.; Jordan, Robert; Lucas, Johna
Abstract : INTRODUCTION: Bremelanotide, an investigational new drug, is a melanocortin 4 receptor agonist that has demonstrated efficacy in the treatment of hypoactive sexual desire disorder (HSDD) in women. In this analysis, bremelanotide efficacy was investigated within age and weight subgroups. METHODS: Women from two phase 3 studies (RECONNECT) and one phase 2 study were separated into age and weight quartiles. After 4-week placebo run-in period, women self-administered 1.75 mg of bremelanotide via auto-injector pen, as desired, or equal volume placebo for 12 (phase 2) or 24 (phase 3) weeks. Efficacy was assessed using FSFI and FSDS-DAO scoring systems, with FSFI desire domain (FSFI-D) and FSDS-DAO distress resulting from low desire (Item 13) as RECONNECT co-primary endpoints. RESULTS: For the total integrated population (N=1337), the difference in FSFI-D mean changes from baseline (bremelanotide-placebo) was 0.38. Differences in mean FSFI-D changes from baseline for each age quartile (n-value range: 150-187) were 0.21 (19-33 y), 0.39 (>33-39 y), 0.56 (>39-44 y), and 0.34 (>44-56 y). Differences in mean FSFI-D changes for each weight quartile (n-value range: 159-181) were 0.30 (39.8-63.1 kg), 0.42 (>63.1-73.5 kg), 0.43 (>73.5-87.6 kg), and 0.34 (>87.6-189.9 kg). Significantly greater (P<0.05) changes in FSFI-D were achieved with bremelanotide vs placebo across all age and weight quartiles. FSDS-DAO Item 13 was also significantly improved across age and weight quartiles with the exception of the 39.8-63.1 kg (P=0.05) weight quartile. CONCLUSION: Bremelanotide demonstrated efficacy in women regardless of age. Bremelanotide significantly improved desire across weight quartiles and showed a trend in decreasing distress.